2006
DOI: 10.1541/ieejfms.126.1128
|View full text |Cite
|
Sign up to set email alerts
|

Treeing Phenomena in Epoxy/Alumina Nanocomposite and Interpretation by a Multi-core Model

Abstract: ObjectivesIn order to clarify how different treeing lifetime and tree growth behavior were between epoxy resins and their nanocomposites, laboratory-prepared epoxy/boehmite alumina nanocomposites were subjected to local high electric filed using treeing test cells, and were evaluated on their treeing performances. Both results experimentally obtained are interpreted based on a multi-core model, and some contradiction in explanation is pointed out for further research. A crossover phenomenon was newly found and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 77 publications
(28 citation statements)
references
References 14 publications
2
26
0
Order By: Relevance
“…The tree does not propagate through the nanoparticles, because they have higher dielectric strength than the polymer matrix, and are more resistant to partial discharges. The electrical tree grows around the nanoparticles forming a zigzag pattern [9][10][11]. Electrical tree can appear under both DC and AC voltages.…”
Section: Present Understanding Of Tree Initiation and Propagationmentioning
confidence: 99%
See 1 more Smart Citation
“…The tree does not propagate through the nanoparticles, because they have higher dielectric strength than the polymer matrix, and are more resistant to partial discharges. The electrical tree grows around the nanoparticles forming a zigzag pattern [9][10][11]. Electrical tree can appear under both DC and AC voltages.…”
Section: Present Understanding Of Tree Initiation and Propagationmentioning
confidence: 99%
“…Partial discharges are the main reason for tree propagation at low electric field, whereas, according to the second model, under higher voltages charge injection and electron avalanches lead to tree propagation, where the tree propagates through the polymer matrix without contacting the nanoparticles [14]. Nanoparticles act as barriers to electrical tree propagation and enforce the tree channels to move around the nanoparticles and not straightforward, not only under the application of AC voltage [9,11] but also under the application of DC voltage [15]. The DC resistivity of epoxy-ZnO nanocomposites increases, while increasing ZnO loading.…”
Section: Present Understanding Of Tree Initiation and Propagationmentioning
confidence: 99%
“…Such agglomerations act as preexisting defects which decrease the interfacial zones. Moreover, such higher filler concentrations enable to form thin channels that connect the opposite electrodes or form clusters of the interacting defects as reported by Tanaka et al [28] and Jonscher and Lacoste [29], respectively. Figure 7 shows the variation of e 0 for the HDPE/ZnO nanocomposites at different concentrations of ZnO NPs as a function of the applied frequency in the range of 1 kHz to 1 MHz.…”
Section: Dielectric Breakdown Strengthmentioning
confidence: 78%
“…With the development of nanotechnology, polymer nanocomposites containing nanosized fillers have drawn much attention, as they are found to have improved properties over pure polymers or polymers filled with micron sized fillers [7][8][9]. Some of the researchers have reported that there is an improvement in electrical treeing resistance of polymers with the addition of inorganic nanofillers [10][11][12][13][14][15][16]. The observed improvement in the properties of nanocomposites depends on several factors.…”
Section: Introductionmentioning
confidence: 99%